Corporate Governance Sebagai Variabel Pemoderasi Dalam Pengaruh Kualitas Laba Terhadap Nilai Perusahaan - esty apridasari (Fakultas Ekonomi Dan Bisnis Islam IAIN Metro, 2019)
The separation of ownership between the principal and agent in a company could cause a conflict of interest where both parties try to maximize their own interests. The mechanism of corporate governance is expected to minimize this conflict of interest. This study examines the corporate governance variables as moderating variable in the influence of earnings quality on firm value. The population of this research is manufacturing company listed on the Indonesia Stock Exchange in 2014-2016 with 66 manufacturing companies and 175 observations as sample. Determination of the sample in this study is carried out by purposive sampling method. Coorporate governance is measured by manajerial ownership, institutional ownership, independent commissioners, and the audit committee), earnings quality is measured by Earnings Response Coefficient (ERC), and the firm value is measured with Price Book Value (PBV). Testing hypotheses using regression analysis. The results show that mangerial ownership has not been proven as moderating variable in the influence of earnings quality on firm value. Institutional ownership, independent board of commissioners, and audit committee could moderate the influence of the earnings quality to firm value.